Revealing seed color variation and their possible association with yield and quality traits in a diversity panel of flax (Linum Usitatissimum L.) - Abtahi, Mozhgan; Mirlohi, Aghafakhr; Sharif-Moghaddam, Negar; Ataii, Ehsan (Frontiers in Plant Science, 2022)
Seed color is a vital quality determinant of flax, significant for consumers’ acceptability and determining the commercial values of seeds. Also, seed color as a phenotypic marker may be a convenient way to select desired plant material. This study assessed a diversity panel representing 144 flax genotypes across diverse geographical origins for the existence of genetic variability for luminosity (L*) and chromaticity (a* and b*) seed color parameters, seed yield, and quality traits over two years. The genetic variance was found to be significant for seed color parameters, demonstrating the presence of significant genetic variability, which provide a resource to objectively evaluate and select flax genotypes with seeds colored according to the market demand. High heritability combined with the high genotypic coefficient of variation was observed for seed yield, oil, and protein content; hence, a better genetic gain is expected upon selecting these traits. Seed yield, seed quality traits, and phenological traits showed significant negative correlation with L* and b* parameters and positive correlation with a* parameter suggesting that the dark background and brown color of the seeds can serve as marker characters to prescreen early-flowering, high yielding and oil and protein-rich genotypes. Interestingly 48 brown-seeded genotypes were identified as early-flowering with short height, large seeds, high thousand seed weight, and capsule diameter. Furthermore, 34 genotypes were characterized by light-colored yellow seeds, large seeds, late-flowering with shorter height, and high branch numbers. Our results highlighted that North America and Australia-belonged genotypes were lighter yellow-seeded than the ones from other continents. Flax genotypes from South America and Asia were high-yielding, while genotypes from North America were low-yielding genotypes. Moreover, darker brown-seeded genotypes have prevailed in the South American continent.